2022
DOI: 10.1111/jgs.17808
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID‐19 pandemic‐related financial challenges on mental health and well‐being among US older adults

Abstract: Background Despite profound financial challenges during the COVID‐19 pandemic, there is a gap in estimating their effects on mental health and well‐being among older adults. Methods The National Health and Aging Trends Study is an ongoing nationally representative cohort study of US older adults. Outcomes included mental health related to COVID‐19 (scores averaged across eight items ranging from one to four), sleep quality during COVID‐19, loneliness during COVID‐19, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Especially, as COVID-bereaved noncitizen immigrants are excluded from FEMA funeral assistance, which could buffer health from the financial impact of bereavement, 29 it is critical to invest resources in Black, Latino, and immigrant communities to prevent disparities in COVID-19 bereavement from extending to even greater disparities in later-life mental health and physical health. 30 AUTHOR CONTRIBUTIONS Alicia R. Riley conceptualized the study, analyzed and interpreted the data, and prepared the first draft of the manuscript; Louise C. Hawkley obtained funding for the data, oversaw data acquisition, interpreted the data, and revised the manuscript; Lissette M. Piedra interpreted the data and revised the manuscript.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, as COVID-bereaved noncitizen immigrants are excluded from FEMA funeral assistance, which could buffer health from the financial impact of bereavement, 29 it is critical to invest resources in Black, Latino, and immigrant communities to prevent disparities in COVID-19 bereavement from extending to even greater disparities in later-life mental health and physical health. 30 AUTHOR CONTRIBUTIONS Alicia R. Riley conceptualized the study, analyzed and interpreted the data, and prepared the first draft of the manuscript; Louise C. Hawkley obtained funding for the data, oversaw data acquisition, interpreted the data, and revised the manuscript; Lissette M. Piedra interpreted the data and revised the manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, better frameworks are needed to account for the intersecting factors shaping Latino health and immigrant health during the pandemic. Especially, as COVID‐bereaved non‐citizen immigrants are excluded from FEMA funeral assistance, which could buffer health from the financial impact of bereavement, 29 it is critical to invest resources in Black, Latino, and immigrant communities to prevent disparities in COVID‐19 bereavement from extending to even greater disparities in later‐life mental health and physical health 30 …”
Section: Discussionmentioning
confidence: 99%
“…When it comes to weight change, and specifically weight loss, older adults represent a particularly vulnerable group. During the pandemic, compared to their younger coworkers, employed older adults were more vulnerable to financial challenges [ 23 , 24 ]. Similarly, retired older adults, many of whom rely on Social Security and have a fixed income, have less economic flexibility to handle unexpected expenses, increasing their sensitivity to financial challenges [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The few prior non-nationally representative studies reported that either summary measures of financial hardship or individual hardships (eg, food insecurity, financial strain) were associated with various measures of sleep health (ie, objectively measured poorer sleep, poor sleep quality, and insomnia symptoms), which is consistent with our findings. 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 31 The 1 nationally representative US study reported a comparable high prevalence of job loss and loss of income/work hours (∼40% vs. 46% in CURB) as well as job loss, loss of income or work hours, and childcare difficulties as cross-sectionally associated with trouble sleeping among US adults from March to April 2020. 16 We expanded upon the literature on this topic by demonstrating associations with additional domain-specific financial hardships (eg, unmet expenses) as well as gender and racial-ethnic disparities in these associations after the second (and highest peak) versus first wave of the pandemic in the US (ie, December 2020 to February 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While prior studies have suggested negative impacts of financial hardship on sleep health (eg, insomnia symptoms, poor sleep quality), 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 to our knowledge, nationally representative US studies to date have yet to investigate potentially differential relationships between financial hardship and sleep during the COVID-19 pandemic by important social determinants of health. 16 To fill this gap in the literature, our aim was to investigate associations between financial hardship and sleep disturbances during the pandemic among a nationally representative sample of US adults and to determine whether associations were modified by gender, race-ethnicity, and both gender and race-ethnicity.…”
Section: Introductionmentioning
confidence: 88%